The Effects of victimization prior to prison on victimization, misconduct, and sanction severity during incarceration - Meade, Benjamin (Crime & delinquency, 2021)
Numerous studies have examined the correlation between physical and/or sexual victimization and offending and re-victimization later in life. However, fewer studies have explored how such victimization affects the adjustment of those incarcerated and the sanctioning decisions of correctional personnel. Using a nationally representative sample of inmates in state prisons, this study utilized hierarchical generalized linear modeling to examine whether victimization prior to incarceration was associated with the likelihood of victimization, misconduct, and sanctioning severity for misconduct during incarceration. Our results confirmed findings of previous research in regards to the victimization and offending/re-victimization relationship. In addition, we discovered that victimization prior to prison is associated with harsher disciplinary sanctioning in prison. Implications of our findings for research and policy are discussed.